THE ROLE OF TRANS SECTORAL SERVICE IN VIOLANCE AGAINST WOMEN AND CHILDREN CASES AT PEKANBARU - Indrayana, Mohammad Tegar; Afandi, Dedi; Fatriah, Syarifah Hidayah (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 2 (2012): Indonesian Journal of Legal and Forensic Sciences, 2012)
Sexual violence against women and domestic violence still very important phenomenon that occurs in all parts of the world today. RS Bhayangkara TK IV in Pekanbaru, is currently one of the places for citizens to obtain service due to violence experienced by women and children to Pekanbaru city and surrounding areas. Each year there are about 1300 cases per year of violence against children and women. Services for domestic violence and violence against women and children served by the Integrated Service Center section or known as PPT in RS Bhayangkara  through Emergency room, and treated by general practitioners who works 24 hours a day. Considering the availability of forensic specialists in Riau province currently only two people, so it is not possible to serve all cases of forensic medicine like RS. Bhayangkara Soekamto or RSUPN Dr. Cipto Mangunkusumo through unit Integrated Crisis Center or also knowns as PKT, in which all cases are handled by a forensic medicine specialist forensics. Particular clinical forensic services for domestic violence and sexual violence against women in RS Bhayangkara TK IV generally been handled for the people who need it though remains to be done continuously.
Keywords: sexual violence against women, domestic violence, forensic riau